Exploring protein interfaces with a general photochemical reagent - Gomez, Gabriela Elena (2006)
Protein folding, natural conformational changes, or interaction between partners involved in recognition phenomena brings about differences in the solvent-accessible surface area (SASA) of the polypeptide chain. This primary event can be monitored by the differential chemical reactivity of functional groups along the protein sequence. Diazirine (DZN), a photoreactive gas similar in size to water, generates methylene carbene (:CH2). The extreme chemical reactivity of this species allows the almost instantaneous and indiscriminate modification of its immediate molecular cage. 3H-DZN was successfully used in our laboratory for studying protein structure and folding. Here we address for the first time the usefulness of this probe to examine the area of interaction in protein-protein complexes. For this purpose we chose the complex formed between hen eggwhite lysozyme(HEWL) and themonoclonal antibody IgG1D1.3. :CH2 labeling of free HEWL or complexed with IgG1 D1.3 yields 2.76 and 2.32 mmol CH 2 per mole protein at 1 mM DZN concentration, respectively. This reduction (15%) becomes consistent with the expected decrement in the SASA of HEWL occurring upon complexation derived from crystallographic data (11%), in agreement with the known unspecific surface labeling reaction of :CH 2. Further comparative analysis at the level of tryptic peptides led to the identification of the sites involved in the interaction. Remarkably, those peptides implicated in the contact area show the highest differential labeling: H15GLDNYR21, G117TDVQAWIR 125, and G22YSLGNWVCAAK33. Thus, protein footprinting with DZN emerges as a feasible methodology useful for mapping contact regions of protein domains involved in macromolecular assemblies.